The economic development of Europe's regions : a quantitative history since 1900 - Wolf, Nikolaus, 1973-; Rosés, Joan R. (New York : Routledge, 2018)
This book is the first quantitative description of Europe's economic development at a regional level over the entire twentieth century. Based on a new and comprehensive set of data, it brings together a group of leading economic historians in order to describe and analyze the development of European regions, both for nation states and for Europe as a whole. This provides a new transnational perspective on Europe's quantitative development, offering for the first time a systematic long-run analysis of national policies independent from the use of national statistical units. The new transnational dimension of data allows for the analysis of national policies in a more thorough way than ever before. The book provides a comprehensive database at the level of modern NUTS 2 regions for the period 1900-2010 in 10-year intervals, and a panoramic view of economic development both below and above the national level. It will be of great interest to economic historians, economic geographers, development economists and those with an interest in economic growth.
Introduction -- Regional economic development in Europe, 1900-2010 : a description of the patterns -- Country chapte -- Austria -- Belgium -- Denmark -- Finland -- France -- Germany -- Italy -- Netherlands -- Norway -- Portugal -- Spain -- Swden -- Switzerland -- United Kingdom and Ireland -- Regional economic development in the United States, 1880 -- 2010 : long-term patterns -- Data appendix.
OCLC-licensed vendor bibliographic record.
Keywords: Economic development -- Europe -- History -- 20th century; Regional planning -- Europe -- History -- 20th century; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Development / Economic Development; Europe -- Economic conditions -- 20th century